What Patient-related Factors Most Strongly Influence Autologous Fat Grafting Volume Retention in Breast Augmentation? - Hiroki Utsunomiya, MD, PhD; Naoki Maruyama, MD, PhD; Takaaki Onodera, MD (Plastic and Reconstructive Surgery, Global Open, 2024)
Background:. Regarding autologous fat grafting for breast augmentation, the factors influencing volume retention are unclear. Few studies have assessed which factors, particularly patient-related variables, could affect volume retention and to what extent, without performing multivariate analysis. In this study, we performed three-dimensional breast volume measurements before and after autologous fat grafting, calculated the volume and volume retention, and investigated factors that may affect volume retention. Methods:. A total of 204 breasts that underwent autologous fat grafting by the same surgeon at our hospital between May 25 and December 25, 2021 were included. Volumetric measurements were taken preoperatively and at 1, 3, and 6 months postoperatively using a three-dimensional camera; volume retention was calculated. Linear mixed model analysis was performed to examine the effects of age, body mass index, number of total autologous fat grafting procedures, pregnancy and lactation history, smoking status, fat processing techniques (sedimentation versus centrifugation), preoperative volume, and weight change at the 3- and 6-month postoperative volume retention analyses. Results:. Using multivariate analysis, the preoperative volume was found to be a significant factor at 3 and 6 months. The preoperative volume affected fat volume retention rate by 0.004 (P = 0.001) and 0.008 (P = 0.011) per 10 mL at 3 and 6 months, respectively. Conclusions:. The preoperative volume likely affected fat volume retention. Specifically, a 100-mL increase in the preoperative breast volume might increase the volume retention by 4%–8%. Preoperative volume is an important confounding factor for future studies.